Impact of Plum pox virus (PPV-D) infection on peach tree growth, productivity and bud cold hardiness. Issue 2 (3rd April 2017) - Samara, Rana; Hunter, David M.; Stobbs, Lorne W.; Greig, Neva; Lowery, D. Thomas; Delury, Naomi C.
Abstract: In 2000, the Dideron (D) strain of Plum pox virus (PPV) was detected in commercial peach and nectarine orchards in the Niagara region of Ontario where most of Canada's stone fruit crops are produced. As part of a disease management research programme, peach ( Prunus persica L. Batsch) trees in a commercial orchard at Niagara-on-the-Lake were assayed for PPV annually for 3 years. The orchard consisted of two blocks of the cultivars 'Allstar' and 'Brighton', of which 4 of 288 and 5 of 252 trees, respectively, were infected with PPV-D. The growth and health of these PPV-infected and non-infected trees were evaluated based on the annual growth rates, vigour (chlorophyll content) and bud winter hardiness. Comparative fruit quantity and quality index values were based on total yield and marketable yield per tree, fruit size and weight, fruit pH, titratable acidity, total soluble solids, flesh firmness, and fruit skin colour. Results from these preliminary studies showed that trees infected with this mild Ontario isolate of PPV produced slightly more fruit of smaller size that ripened earlier than non-infected trees. However, yield efficiencies based on weight of fruit relative to the trunk cross-sectional area did not differ statistically. Screenhouse studies on three graft-inoculated fresh market peach cultivars ('Babygold', 'Catherina', and 'Garnet Beauty') similarly did not demonstrate any differences in growth or fruit production in the second and third year post inoculation, but fruit on infected trees matured somewhat earlier.